To be or Not to be Threatening, but What was the Question? Biased Face Evaluation in Social Anxiety and Depression Depends on How You Frame the Query - Lange, Wolf-Gero; Rinck, Mike; Becker, Eni S. (Frontiers in Psychology, 2013)
Scientific evidence is equivocal on whether Social Anxiety Disorder (SAD) is characterized by a biased negative evaluation of facial expressions, even though it is assumed that such a bias plays a crucial role in the maintenance of the disorder. The way of framing the evaluation question may play an important role in the inconsistencies of earlier results. To investigate this issue, an unselected sample of 95 participants (11 male) with varying degrees of social anxiety and depressive symptoms rated facial crowds with different ratios of neutral-disgust, neutral-sad, neutral-happy and neutral-surprised expressions in terms of friendliness, approval, difficulty to make contact, and threat. It appeared that the impact of social anxiety on ratings was highly dependent on the type of question that was asked, but not on the type of emotion that was shown: A high degree of social anxiety was related to a more positive evaluation of crowds when friendliness was assessed. When asking about the difficulty to make contact, social anxiety was related to more difficulty. When the threat evoked by a crowd had to be evaluated, higher degrees of social anxiety were tendentiously correlated with higher threat ratings. Degree of depression, on the other hand, was negatively correlated only to approval-ratings. In addition, with an increasing degree of depression, the negative impact that any additional emotional face had on approval ratings increased as well. The theoretical and methodological implications of the results are discussed.